2009
DOI: 10.1146/annurev.immunol.021908.132715
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammasomes: Guardians of the Body

Abstract: The innate immune system relies on its capacity to rapidly detect invading pathogenic microbes as foreign and to eliminate them. The discovery of Toll-like receptors (TLRs) provided a class of membrane receptors that sense extracellular microbes and trigger antipathogen signaling cascades. More recently, intracellular microbial sensors have been identified, including NOD-like receptors (NLRs). Some of the NLRs also sense nonmicrobial danger signals and form large cytoplasmic complexes called inflammasomes that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
2,034
1
58

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,151 publications
(2,112 citation statements)
references
References 264 publications
(243 reference statements)
19
2,034
1
58
Order By: Relevance
“…ASC recruits pro-caspase 1 to the inflammasome, where it is converted to caspase 1, which leads to cleavage of pro-IL-1b and secretion of mature IL-1b. 2 Genetic studies in mice have shown that IL-1b activation by muramyl dipeptide requires both NOD2 and NALP3, suggesting that these proteins may cooperate indirectly or directly to trigger an immune response. 3 CARD8 is a potent suppressor of several NF-kb activating signals and thus limits the duration of NFkB-mediated gene transcription.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ASC recruits pro-caspase 1 to the inflammasome, where it is converted to caspase 1, which leads to cleavage of pro-IL-1b and secretion of mature IL-1b. 2 Genetic studies in mice have shown that IL-1b activation by muramyl dipeptide requires both NOD2 and NALP3, suggesting that these proteins may cooperate indirectly or directly to trigger an immune response. 3 CARD8 is a potent suppressor of several NF-kb activating signals and thus limits the duration of NFkB-mediated gene transcription.…”
Section: Resultsmentioning
confidence: 99%
“…CARD8 interacts with the NACHT-LRR receptor NALP3 (also known as cryopyrin, NLRP3 or PYPAF1), and Apoptosis-associated Speck-like protein containing a CARD to form a caspase 1 activating complex termed the NALP3 inflammasome, which mediates the production and secretion of interleukin (IL)-1b in response to microbial challenge ( Figure 1). 1,2 . In addition to its role in the inflammasome, CARD8 is also a potent inhibitor of nuclear factor (NF)kB, and it has been suggested that 'cross-talk' occurs between CARD8, NALP3 and nucleotide-binding oligomerization domain protein 2 (NOD2, also known as CARD15) 2,3 As overproduction of IL-1b and dysregulation of NFkB are hallmarks of Crohn's disease (CD), 4 it is not surprising that CARD8 was considered an attractive candidate risk gene for IBD immediately following the identification of IBD6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The release of IL-1β and IL-18 can result in the activation of an acute inflammatory response, resulting in the production of TNF-α, interferon- (IFN-) as well as chemotaxis of immune cells, and induction of tissue injury. In order to obtain full activation (that is, to obtain the effective synthesis and release of active IL-1β and IL-18) the inflammasome typically requires two distinct signals: i) a first priming signal usually triggered either by PAMPs interacting with PRRs as well as by inflammatory citokines (TNF or IL-1) interacting with the related receptor; the first signal is designed to activate transcription of the genes encoding pro-IL-1β, pro-IL-18 and NLRP3 [110]; ii) the second signal can be provided by various inflammasome ligands (including PAMPs) through involvement/activation of cytosolic NLR (NOD-like receptor) proteins, particularly NLRP3, which in turn leads to activation of caspase-1 and cleavage of pro-IL-1β and pro-IL-18 into the active forms [111]; the second signal can be reinforced by ROS generated after exposure to PAMPs and DAMPs. Inflammasome can be modulated by at least two further events: a) it has been reported that a cross-talk exists between inflammasome and autophagy; in particular, autophagic suppression of ROS generation (i.e., by sequestering in autophagosomes defective mitochondria which may represent a source of ROS) indirectly inhibits inflammasome activity [112]; b) inflammasome activity is inhibited by either cell-cell interactions or secreted factors (for example IFN) involving lymphocytes of adaptive immunity, particularly CD4+ effector and memory T cells [113].…”
Section: Inflammasomes and Liver Fibrogenesismentioning
confidence: 99%
“…2010. 40: 595-653 LPS-primed human and murine DC in vitro [10], a reminder of the doublestep requirement for inflammasome activation triggered by other particulates, such as silica or asbestos [11]. The following year, it was found that uric acid is induced by alum in vivo and is responsible for alum immunostimulatory properties, suggesting a possible, indirect involvement of the NLRP3 inflammasome [5], which can be activated by monosodium urate (MSU) crystals [12].…”
mentioning
confidence: 99%